If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -12 = 8x + 42 Reorder the terms: -12 + 10x = 8x + 42 Reorder the terms: -12 + 10x = 42 + 8x Solving -12 + 10x = 42 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -12 + 10x + -8x = 42 + 8x + -8x Combine like terms: 10x + -8x = 2x -12 + 2x = 42 + 8x + -8x Combine like terms: 8x + -8x = 0 -12 + 2x = 42 + 0 -12 + 2x = 42 Add '12' to each side of the equation. -12 + 12 + 2x = 42 + 12 Combine like terms: -12 + 12 = 0 0 + 2x = 42 + 12 2x = 42 + 12 Combine like terms: 42 + 12 = 54 2x = 54 Divide each side by '2'. x = 27 Simplifying x = 27
| 2a=5b+1 | | 61=7(-1+2v)+2 | | 2x^2-8x=152 | | d=20(35) | | -33+4n=4(n+4)+7n | | 1/3m=14 | | 2.43=log(x) | | -33+4n=4(n+7)+7n | | 3m+100=10 | | -1=2(3x-4)+x | | 2(8x-5)=2x-(-18) | | d=35(10) | | 2b^2-18b+116=0 | | -5g=15 | | 180=-6(7-5x) | | 0.6(x+200)=0.68-448 | | -2-8=-7+x | | 18=not-18 | | 4/7×21/40 | | 8a-(16/12a)=14 | | 2/i= | | d=5(55) | | 2x-3*2= | | 4x-9y-6x+6y= | | 5-2ab-3bc+a*3b-c*b*4= | | 17/3x=1 | | 5x+5+3x+13=90 | | 2.6(m+1.9)=22 | | 5000/x=300 | | -2y=x-3 | | 2727/g=27 | | 6x-1=x+28 |